228 Outcomes of Gallstone Complications During the COVID Pandemic. (12th October 2021) - Isherwood, J; Karki, B B; Chung, W Y; AlSaoudi, T; Wolff, J; Malde, D; Bhardwaj, N; Garcea, G; Dennison, A
Abstract: Background: The Intercollegiate General Surgery Guidance on COVID-19 recommended either non-surgical management or cholecystostomy drains for the management of acute biliary disease replacing gold standard practice of early laparoscopic cholecystectomy within 1 week of index admission with drainage reserved for high-risk patients where surgery is not appropriate. Method: This is the retrospective study presenting the impact of gallstone disease in our unit during five months of the COVID- 19 pandemic (March 2020-August 2020) compared with the equivalent period in 2019. Results: Patients presenting to the HPB unit with a coded diagnosis of gallstones were included and during the study period 1447 patients presented compared with 1413 in 2019. In 2020 compared with 2019 there was a significant decrease in patients presenting with cholecystitis (240 vs 313; p = 0.031) but no significant difference in patients presenting due to gallbladder perforation (44 vs 51). Interestingly the numbers of cholecystostomies were comparable, with 11 in 2020 and 15 in 2019 representing significantly less than the 7.2% figure published by Peckham-Cooper et al. Conclusions: In our study there was a decrease in patients with cholecystitis and perforation and there was an increase in patients with gallstone pancreatitis, increase waiting lists with increase in the incidence of serious complications. In our trust we currently have 656 patients awaiting cholecystectomy compared to 280 in august 2019. With the recent elevation of the alert level to 4 and increased government restrictions, a consistent National approach is required to mitigate these risks.